Regional fisheries management: Virtual decision making in a pandemic. (March 2021) - Haas, Bianca; Davis, Ruth; Hanich, Quentin
Abstract: The global COVID-19 pandemic is impacting on the fisheries sector and posing significant challenges for the management of transboundary fisheries. Due to travel bans and border closures, regional organizations are not able to hold face-to-face meetings. This commentary provides a summary of the meeting procedures of Regional Fisheries Management Organizations and Regional Organizations during the global pandemic. Most organizations have transitioned to online platforms and are holding virtual meetings. These online meetings impose significant challenges concerning sustainable fisheries management, such as limited discussions and negotiations on important issues. Thus to continue their work effectively, these organizations need to develop new decision-making procedures that are more resilient in the upcoming future.